Review of Resilience Conceptual , Assessment and Intervention - Yang, Zongsheng (Pacific International Journal, 2023)
Resilience is a crucial resource for promoting the development of both mental and physical health. Researchers have divided resilience into three main categories, namely qualitative definition, outcome definition, and process definition, depending on their perspective. Typically, resilience is evaluated using resilience scales and emotional scales, and interventions can be carried out through social movements, community education, school education, individual counseling, and group counseling. Protective factors in resilience facilitate effective coping with negative events and promote healthy physical and mental development. The aim of this study is to review the existing research on the concept, assessment, and intervention of resilience and to identify future research directions. These directions include clarifying the connotation and extension of the concept, constructing the assessment index system, exploring the mechanism of action, expanding the coverage groups and contents, combining the theory and empirical evidence related to resilience and mental health literacy, and conducting in-depth research to improve the overall health and well-being of the public.